PENGARUH MEDIA GAMBAR SERI TERHADAP KETERAMPILAN MENULIS KARANGAN SEDERHANA MUATAN BAHASA INDONESIA KELAS III SDN DESA TANJUNG PUTUS - Dwi Novri Asmara; Antik Estika Hader; Mia Sartika Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Problems in learning Indonesian in the discussion of simple essay writing material, where students lack interest in writing simple essays, students' knowledge is still little about writing simple essays, students who find it difficult to arrange sentences into a paragraph. Through this problem, the purpose of this study is to overcome the low skills of writing simple essays. To overcome this, interesting and appropriate media are needed so that students can easily understand the material. Therefore, researchers will apply serial image media. The type of research used was experimental, Quasi-Experiential Design. This research was carried out at SDN 128 Tanjung dropping out of class III and SDN 238 Tanjung dropping out of class III in the even semester of the 2022/2023 school year. The population in this study were 17 elementary school students from the two elementary schools. The data collection instrument used uses independent and dependent variables. Development of instruments used validity test, reliability test, level of difficulty test. Data collection techniques used pre-test (pre-test) and post-test (post-test). Data analysis techniques in this study used the Normality Test, homogeneity test and hypothesis testing. Based on the results obtained, the significance of the paired samples t test is 0.002 <0.05, which means that Ho is rejected and Ha is accepted. So it can be concluded from the experimental class and the control class, that the experimental class has the influence of serial picture media on student learning outcomes in Indonesian Language Theme 8 SDN 128 Tanjung Bawah, because the experimental class meets the criteria, while the control class does not meet the criteria.